2019
DOI: 10.3851/imp3351
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Neuropsychiatric Tolerability of Bictegravir Combined with Emtricitabine/Tenofovir Alafenamide in Clinical Practice

Abstract: Background Neuropsychiatric AEs (NPAEs) leading to dolutegravir (DTG) discontinuation were seen more frequently in real-world use than in randomized clinical trials (RCTs). The recently approved fixed-dose combination bictegravir plus emtricitabine and tenofovir alafenamide (BIC/F/TAF) has shown comparable NPAE rates but some favourable patient-reported outcomes in RCTs compared with DTG. We were interested in its neuropsychiatric tolerability in clinical practice. Methods All patients starting BIC/F/TAF fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…12 Conversely, in analysis of routine clinical care, treatment discontinuation rates due to neuropsychiatric events were comparable between dolutegravir and bictegravir (P = 0.31). 14 These findings underscore the importance of selecting an initial ART regimen that does not have the propensity to cause or worsen NPEs. Data from a recent analysis of a phase 3 study of treatment-naïve patients starting a darunavir-based single-tablet regimen showed that patients with baseline neuropsychiatric comorbidities, versus those without, did not experience a higher incidence of new-onset study drug-related neurologic (5% in both cohorts) or psychiatric (1% vs 3%) adverse events, suggesting that a darunavir-based singletablet regimen may be a suitable option for this patient population.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…12 Conversely, in analysis of routine clinical care, treatment discontinuation rates due to neuropsychiatric events were comparable between dolutegravir and bictegravir (P = 0.31). 14 These findings underscore the importance of selecting an initial ART regimen that does not have the propensity to cause or worsen NPEs. Data from a recent analysis of a phase 3 study of treatment-naïve patients starting a darunavir-based single-tablet regimen showed that patients with baseline neuropsychiatric comorbidities, versus those without, did not experience a higher incidence of new-onset study drug-related neurologic (5% in both cohorts) or psychiatric (1% vs 3%) adverse events, suggesting that a darunavir-based singletablet regimen may be a suitable option for this patient population.…”
Section: Discussionmentioning
confidence: 93%
“…10 Certain ART regimens have been associated with an increased risk of NPEs, but the extent varies even among agents in the same class. 1,5,[11][12][13][14] Findings from a phase 3b equivalence study evaluating ritonavir-boosted atazanavir versus efavirenz indicate that ritonavir-boosted atazanavir had a lower incidence of neuropsychological adverse events, including depression, dizziness/lightheadedness, and insomnia than efavirenz across two different nucleoside reverse transcriptase inhibitor backbones. 15 In a pooled analysis of phase 3 studies of two non-nucleoside reverse transcriptase inhibitor-based regimens, the incidence of treatment-related neuropsychiatric adverse events was significantly higher with efavirenz than rilpivirine (any cause: 57% vs 40%, P < 0.0001; treatment-related: 48% vs 27%, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cohort studies reported a higher rate of discontinuation of DTG due to neuropsychiatric adverse events in comparison with other INSTIs. However, a recent study showed that the short-term tolerability of BIC/FTC/TAF was comparable to DTG-containing regimens, with a low rate of cross-intolerance between the two INSTIs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For other INSTIs such as raltegravir (RAL) and elvitegravir (EVG), the incidence of CNS toxicity reports seems lower in the literature [ 22 , 23 ]. At the same time, for bictegravir (BIC), observational data are still scarce [ 24 ], but for all of them, CNS-AEs have been signaled in the literature with variable incidence [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%